2013
DOI: 10.1364/ao.52.005835
|View full text |Cite
|
Sign up to set email alerts
|

Feedback phase correction of Bessel beams in confocal line light-sheet microscopy: a simulation study

Abstract: Confocal line detection has been shown to improve contrast in light-sheet-based microscopy especially when illuminating the sample by Bessel beams. Besides their self-reconstructing capability, the stability in propagation direction of Bessel beams allows to block the unwanted emission light from the Bessel beam's ring system. However, due to phase aberrations induced especially at the border of the specimen, Bessel beams may not propagate along lines parallel to the slit detector. Here we present a concept of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…14,15 It has also been suggested that dynamic elements could be used to control the illumination profile of a line scan illumination system for light sheet microscopy. 55 Micro-endoscopy Micro-endoscopes are attracting interest due to their potential in enabling optical biopsy for a range of clinical and research applications. The challenge in such systems is to perform high resolutionpossibly three-dimensional-imaging via a narrow endoscopes, whose dimensions constrain significantly the optical design.…”
Section: Light Sheet Microscopesmentioning
confidence: 99%
“…14,15 It has also been suggested that dynamic elements could be used to control the illumination profile of a line scan illumination system for light sheet microscopy. 55 Micro-endoscopy Micro-endoscopes are attracting interest due to their potential in enabling optical biopsy for a range of clinical and research applications. The challenge in such systems is to perform high resolutionpossibly three-dimensional-imaging via a narrow endoscopes, whose dimensions constrain significantly the optical design.…”
Section: Light Sheet Microscopesmentioning
confidence: 99%
“…The use of Bessel‐beam illumination has recently been investigated for a variety of volumetric microscopy approaches . Specifically, for light sheet microscopy, the propagation‐invariant (“diffraction‐free”) property of the main lobe of a Bessel beam is valuable to generate a large depth of focus.…”
Section: Introductionmentioning
confidence: 99%
“…The "non-diffracting" property of a Bessel beam refers to its ability to propagate over a long distance along the optical axis without exhibiting any broadening or bending of its main lobe [1][2][3]. The "self-reconstructing" property refers to the ability of this main lobe to propagate through highly heterogeneous media, even in the presence of obstructions that may block or distort the main lobe temporarily [2,4,11]. This self-healing behavior is aided by the fact that each side lobe of a Bessel beam carries approximately the same amount of energy as the main lobe and continuously acts to reconstruct the main lobe as it propagates [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…When performing light-sheet microscopy with conventional Gaussian illumination in tissues, the field of view (FOV), within which the thickness of the light sheet is fairly uniform, is restricted and may be approximated by the confocal parameter, or twice the Rayleigh range of the Gaussian beam [2,5,6]. In addition, tissue-heterogeneity-induced light-sheet distortions have been shown to diminish the contrast and resolution in Gaussian light-sheet-based microscopy [1,11]. The "non-diffracting" and "self-reconstructing" characteristics of a Bessel beam have shown promise for reducing the limitations mentioned above [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%